The integrated disease surveillance and response system in northern Ghana: challenges to the core and support functions - Adokiya, Martin Nyaaba; Awoonor-Williams, John K.; Beiersmann, Claudia; Müller, Olaf (BMC health services research, 2015)
The integrated disease surveillance and response (IDSR) strategy was adopted in Ghana over a decade ago, yet gaps still remain in its proper functioning. The objective of this study was to assess the core and support functions of the IDSR system at the periphery level of the health system in northern Ghana.
Gesehen am 04.11.2020